The prevalence of sexually transmitted diseases among prostitutes in Malaysia. - Ramachandran, S (1990)
The prevalence of sexually transmitted diseases was determined among 370 prostitutes in Kuala Lumpur, Malaysia. Chlamydial cervicitis (26.5%) was detected more frequently than gonorrhoea (14.25%) and was associated more often with pelvic inflammatory disease. Concurrent infections and asymptomatic infections were common. Seropositivity to hepatitis B and syphilis were 66.3% and 13.6% respectively. Women under 20 years of age had significantly higher rates of infection with Chlamydia trachomatis and hepatitis B virus than older women.